2017
DOI: 10.1038/s41598-017-12744-2
|View full text |Cite
|
Sign up to set email alerts
|

Schwann cells promote post-traumatic nerve inflammation and neuropathic pain through MHC class II

Abstract: The activation of T helper cells requires antigens to be exposed on the surface of antigen presenting cells (APCs) via MHC class II (MHC-II) molecules. Expression of MHC-II is generally limited to professional APCs, but other cell types can express MHC-II under inflammatory conditions. However, the importance of these conditional APCs is unknown. We and others have previously shown that Schwann cells are potentially conditional APCs, but the functional relevance of MHC-II expression by Schwann cells has not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 45 publications
2
50
0
1
Order By: Relevance
“…Moreover, the progressing death of ganglionic-like tumor cells and resulting axon degeneration observed in GNBs/GNs (Li & Nakagawara, 2013) In addition to their influence on tumor cells, stromal SCs also hold a considerable potential to modulate the tumor microenvironment. We identified that stromal SCs express MHC-II receptors and chemokines, and confirmed the presence of immune cells in GN sections, which is in line with the increasing reports about the immunomodulatory potential of SCs during nerve regeneration and peripheral neuropathies (Baetas-da-Cruz et al, 2009;Bergsteinsdottir et al, 1991;Hartlehnert et al, 2017;Horste et al, 2010;Martyn et al, 2019;Weiss et al, 2016;Ydens et al, 2013). Furthermore, the shared expression signature of stromal/repair SCs contained basement membrane components and ECM remodelers such as metalloproteinases and matricellular proteins.…”
Section: Schwann Cell Plasticitysupporting
confidence: 88%
“…Moreover, the progressing death of ganglionic-like tumor cells and resulting axon degeneration observed in GNBs/GNs (Li & Nakagawara, 2013) In addition to their influence on tumor cells, stromal SCs also hold a considerable potential to modulate the tumor microenvironment. We identified that stromal SCs express MHC-II receptors and chemokines, and confirmed the presence of immune cells in GN sections, which is in line with the increasing reports about the immunomodulatory potential of SCs during nerve regeneration and peripheral neuropathies (Baetas-da-Cruz et al, 2009;Bergsteinsdottir et al, 1991;Hartlehnert et al, 2017;Horste et al, 2010;Martyn et al, 2019;Weiss et al, 2016;Ydens et al, 2013). Furthermore, the shared expression signature of stromal/repair SCs contained basement membrane components and ECM remodelers such as metalloproteinases and matricellular proteins.…”
Section: Schwann Cell Plasticitysupporting
confidence: 88%
“…Compared with CD11b -F4/80nonmacrophage cells, CD11b + F4/80 + macrophages expressed more CD80, CD86, and MHCII ( Figure 6, F-H). CD11b -F4/80non macrophage cells from sciatic nerves of NOD.Aire GW/+ mice expressed an intermediate amount of MHCII ( Figure 6H), which may reflect an upregulation of MHCII expression by other cell types such as Schwann cells (51)(52)(53). These data suggest that nerve-infiltrating macrophages are heterogeneous, expressing both M1-and M2-associated markers, and express markers of activation.…”
Section: Resultsmentioning
confidence: 91%
“…However, it remains uncertain whether these αβ T cells are CD4 + αβ T cells and even MHCIIrestricted Th cells. Recently, CD4 + cells were shown to robustly infiltrate into the injured nerves after adult mice CCI or PSNL [115,116], and the infiltration of CD4 + cells into chronically constricted sciatic nerves are dependent on MHCII specifically expressed on Schwann cells [115]. This suggests the potential infiltration of CD4 + αβ T cells and even Th cells into the injured nerves, which needs further validations.…”
Section: Classical Pathogenic Neuroimmune Interfacesmentioning
confidence: 99%
“…Hence, the injured nerves are not a necessary neuroimmune interface for αβ T cells, including possible Th cells, to initiate the development of chronic tactile allodynia after nerve injuries. This notion needs further validation via region-specific cell targeting in a different set of nerve injury models, such as CCI, in which intact peripheral axons of primary sensory neurons (PSNs) transmitting tactile allodynia are mixed with degenerating peripheral axons of axotomized PSNs [115][116][117]. However, the number of αβ T cells in the injured nerves was shown to have no correlation with the intensity of tactile allodynia after adult rat CCI to the sciatic nerve [105].…”
Section: Classical Pathogenic Neuroimmune Interfacesmentioning
confidence: 99%